(NsOC)QÆALXNA PSIHOLOGÆQ (B:s)E (NPOS)QÆBNIK (B/s)E - (NoRBAN(B-(NlEMBRIK(B, (Nl)QÆDÆQ eRNESTÆWNA(B,s)E ((NkI)QÇW (B:s)E (NaKADEMWIDAW(B,s, 2003)
(Nw POS)QÆBNIKU ROZKRITO ÆSTORI^NIJ ROZWITOK SOCÆALXNO(B-(NPSIHOLOGÆ^NIH ÆDEJ(B, (NOHARAKTERIZOWANO PROWÆDNÆ NAPRQMI PRIKLADNOÇ SOCÆALXNOÇ PSIHOLOGÆÇ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NsOC)QÆALXNA PSIHOLOGÆQs)E; (NSOC)QÆALXNA PSIHOLOGÆQs)E; (NSOC)QÆALÆZACÆQs)E; (NSOC)QÆALXNA USTANOWKAs)E; (NSP)QÆLKUWANNQs)E; (NSOC)QÆALXNA PSIHOLOGÆQ GRUPs)E; (NM)QÆVOSOBISTÆSNA WZAÃMODÆQs)E; (NGRUPOWA DINAM)QÆKAs)E; (NPRIKLADNA SOC)QÆALXNA PSIHOLOGÆQs)E